A Better World for All : Progress Toward the International Development Goals. (International Monetary Fund, 2000)
This paper focuses on goal setting for development of the world. The paper highlights that the goals come from the agreements and resolutions of the world conferences organized by the United Nations in the first half of the 1990s. The paper focuses on seven goals that cover poverty, education, gender equality, infant and child mortality, maternal mortality, reproductive health, and environment. Each of the seven goals addresses an aspect of poverty. The paper also emphasizes that these goals should be viewed together because they are mutually reinforcing.